Advances in the Mechanisms Affecting Meniscal Avascular Zone Repair and Therapies - Yan, Wenqiang; Dai, Wenli; Cheng, Jin; Fan, Yifei; Wu, Tong; Zhao, Fengyuan; Zhang, Jiahao; Hu, Xiaoqing; Ao, Yingfang (Frontiers in Cell and Developmental Biology, 2021)
Injuries to menisci are the most common disease among knee joint-related morbidities and cover a widespread population ranging from children and the general population to the old and athletes. Repair of the injuries in the meniscal avascular zone remains a significant challenge due to the limited intrinsic healing capacity compared to the peripheral vascularized zone. The current surgical strategies for avascular zone injuries remain insufficient to prevent the development of cartilage degeneration and the ultimate emergence of osteoarthritis (OA). Due to the drawbacks of current surgical methods, the research interest has been transferred toward facilitating meniscal avascular zone repair, where it is expected to maintain meniscal tissue integrity, prevent secondary cartilage degeneration and improve knee joint function, which is consistent with the current prevailing management idea to maintain the integrity of meniscal tissue whenever possible. Biological augmentations have emerged as an alternative to current surgical methods for meniscal avascular zone repair. However, understanding the specific biological mechanisms that affect meniscal avascular zone repair is critical for the development of novel and comprehensive biological augmentations. For this reason, this review firstly summarized the current surgical techniques, including meniscectomies and meniscal substitution. We then discuss the state-of-the-art biological mechanisms, including vascularization, inflammation, extracellular matrix degradation and cellular component that were associated with meniscal avascular zone healing and the advances in therapeutic strategies. Finally, perspectives for the future biological augmentations for meniscal avascular zone injuries will be given.